PEMBELAJARAN MELALUI MEDIA GEOGEBRA DALAM MENGKONSTRUKSI GRAFIK GEOMETRI DENGAN PENEMUAN TERBIMBING - Nur Farida; Rosita Dwi Ferdiani; Tatik Retno Murniasih (INSPIRAMATIKA, 2022)
The purpose of this study is to improve students' understanding in constructing geometric graphs through geogebra media with the guided discovery method. In mathematics learning, the teacher-oriented expository method often uses which does not provide opportunities for students to construct their own mathematical ideas so that students become passive learners. Students are still confused about using mathematical concepts because students only memorize the concepts, not understand them. This type of research is an experiment with data collection techniques through student activity observation sheets and learning outcomes tests. The subjects in this study were students. The results of this study indicate the application of the guided discovery method of geogebra media can increase student activity and student learning outcomes of mathematics. Student activities are enhanced by the use of geogebra media in constructing graphs. Based on the results of the student's final test showed 83.33%, it can be concluded that learning through geogebra media in constructing geometric graphs with guided discovery is very effective in increasing student understanding of geometric material and can activate student thinking patterns.